Induction of apoptosis in the human Leukemic U937 cell line by Kaempferia parviflora Wall.ex.Baker extract and effects of paclitaxel and camptothecin. - Banjerdpongchai R. (2014)
Kaempferia parviflora Wall.ex.Baker is a Thai medicinal herb that has high antioxidant and anti-inflammatory activities. Apoptotic effects of the herbal extract alone and in combination with chemotherapeutic drugs, paclitaxel and camptothecin, were here studied in the human promonocytic leukemic U937 cell line. K. parviflora extract suppressed cell proliferation and decreased cell viability in a dose- and time-dependent manner as assessed using the trypan blue exclusion assay. Staining of extract-treated cells with propidium iodide and examination under a fluorescence microscope showed condensed nuclei and apoptotic bodies. Mitochondrial transmembrane potential (MTP) decreased after treatment and the number of cells with decreased MTP also increased. Furthermore, activation of caspase-3 was found in herbal extract-treated cells. When the extract was combined with paclitaxel, an additive effect on U937 cell apoptosis was obtained, whereas camptothecin exerted an antagonistic effect.